Cultural influences on attitudes about the causes and consequences of wildlife poaching - Rizzolo, Jessica Bell (Crime, law and social change, 2017)
The extant poaching literature has been criticized as an overly static way of profiling offenders and predicting crime, since the categorization of environmental crime is contingent on the social context as much as offender motivations. Cultural factors have the potential to affect both poaching practices and societal responses to poaching. Cultural risk theory proposes that risk perceptions are shaped by two dimensions: the level of affiliation between individuals (group) and the prescriptiveness of norms (grid). Using quantitative survey data (N = 49) from stakeholders living near Analamazaotra Special Reserve in Madagascar (2013), we analyzed how prescriptiveness of norms at different levels of affiliation affected motivations to poach and not to poach and perceived impacts of poaching on people and the environment. Malagasy laws were a more significant deterrent to poaching than fokonolona rules. The pre-colonial fokonolona was consistent with an equalitarian cultural type and influenced beliefs about the human consequences of poaching, whereas the post-colonial Madagascar National Parks adhered to a hierarchical cultural type and had a robust effect on the perceived environmental impacts of poaching. Implications for environmental crime in Madagascar and cultural risk theory are discussed.